The Correlation Of Mastering The Simple Past Tense And Students’ Ability Writing Recount Text By 10th Grade High School Of Sma Pgri 1 Bekasi - Arasy, Aida Silmi (Arus Jurnal Psikologi dan Pendidikan, 2025)
This study aims to examine and describe the ability of tenth-grade students at SMA PGRI 1 Bekasi to write recount texts in a structured and accurate manner using the simple past tense. The research focuses on the students’ mastery of the simple past tense and its relationship to their writing skills, specifically among students of classes X-6 and X-7, totaling 73 participants. The method employed is Classroom Action Research, conducted in collaboration with the English teacher. The research applies a quantitative approach with a correlational design. Data were collected through multiple-choice tests and written assessments to measure both the mastery of the simple past tense and the students’ ability to write recount texts. The test results showed that the average score for simple past tense mastery was 12.25, with a median of 13.00, a mode of 14, and a standard deviation of 2.866. Referring to the t-distribution table for a sample size of n = 73 and a significance level of α = 5%, the critical t-value was approximately 0.232. Although Pearson’s correlation test generally relies directly on the r value and its significance, this comparison was used analogically to support the explanation. Since rₓᵧ = 0.870 > t-table, it can be concluded that the null hypothesis (H₀) is rejected, and the alternative hypothesis (H₁) is accepted. Therefore, there is a positive and significant relationship between students’ mastery of the simple past tense and their ability to write recount texts effectively.